Study on the persistence of ciprofloxacin and sulfamethoxazole in simulated drinking water systems - Victoria Rilstone; Yves Filion; Pascale Champagne (Environmental Systems Research)
Abstract The antibiotics ciprofloxacin and sulfamethoxazole are well-known to be persistent in drinking water, as they have been detected at the highest concentration and frequency, respectively. These antibiotics persist despite their residence time, water treatment, and environmental conditions encountered in drinking water distribution systems. To better understand this phenomenon, the objectives of this study were to determine their degradation kinetics at a residual, sub-minimum inhibitory concentration while exposed to multi-species biofilms in polyvinyl chloride (PVC) pipe, as well as examine their effect on total cell count (TCC). The results revealed that both antibiotics continued to be detected after the experimental period of 12 days. Ciprofloxacin concentrations decreased by 31.1% (± 3.9%) and 27.4% (± 7.7%) during exposure to the biofilm and PVC-only control respectively, whereas sulfamethoxazole concentrations decreased by 87.2% (± 15.8%) and 3.6% (± 8.6%) during exposure to the biofilm and PVC-only control, respectively. Biofilm TCC increased significantly when exposed to ciprofloxacin (p-value < 0.005), but showed no significant change when exposed to sulfamethoxazole (p-value > 0.05), which suggested that ciprofloxacin enhanced biofilm formation. These results address the gap in antibiotic persistence research by tracing their concentrations, elucidating the mechanisms of sorption and degradation, and discussing their relative implications. As antibiotics continue to persist in drinking water, their interaction with biofilms may contribute to the long-term selection of antibiotic-resistant bacteria, posing potential risks to drinking water safety and public health.